The Effect Of Current Ratio, Debt To Equity Ratio And Sales Growth On Financial Distress - Nursyamsiah; Putri Dwi Wahyuni (DINASTI RESEARCH, 2024)
The purpose of this study was to prove the hypothesis that current ratio, debt to equity ratio and sales growth affect financial distress. This type of research uses a quantitative approach. The population in this study were real estate and property companies listed on the IDX in 2017-2021. The total population was 79 companies. Researchers apply a non-probability sampling method, which specifically will be carried out using purposive sampling method, then a total sample of 15 companies is found. The data collection technique used in this exploration is the documentation strategy. Then the data analysis uses multiple linear regression analysis methods to analyze the effect of independent variables on the dependent which is processed using the Statistical Program for Social Science (SPSS) 22 software program. Based on hypothesis testing, the results show that current ratio and sales growth have no significant effect on financial distress. Meanwhile, debt to equity ratio has a negative and significant effect on financial distress.